STUDI KELAYAKAN FINANSIAL DESA WISATA GUWOSARI - Novi Diah Wulandari; Henda Resti Fatmaningrum2; Rifqi Syarif Nasrulloh (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Guwosari village has a well-known historical tour, namely Selarong Cave which is thesite of Prince Diponegoro's petilasan. In the economic sector, Guwosari Village has awell-known culinary potential, namely ingkung ayam. There are 8 culinary industries inthe form of ingkung stalls which are quite well known both locally and nationally. Interms of handicrafts, Guwosari Village has mainstay commodities of coconut shellcrafts, wood crafts and sungging arrangements, with the superior commodities beingbamboo and blangkon. This study aims to analyze the financial feasibility of developingGuwosari tourism village, especially Banjaran Hamlet, using the NPV IRR PBP andNET B / C methods. data collection methods using interviews and observations andprocessed to produce cash flow calculations. The results of this study indicate that NPV>0, IRR = 28%, NET B / C> 1. With a PBP of 5.7 years, this shows that the developmentof the tourist village of Guwosari can be done